Uso do método do padrão interno em sistemas FIA e BIA e determinação simultânea de diclofenaco e codeína em formulações farmacêuticas por amperometria de múltiplos pulsos - Gimenes, Denise Tofanello (2013)
The present thesis demonstrates, for the first time, the possibility of using of the internal standard method in FIA or BIA systems with amperometric detection. The method allows to obtain accurate results in the presence of fluctuations in the system parameters (injected volume, dispensing rate, ionic strength and accidental insertion of air bubbles) and in the presence of contamination and/or gradual passivation of the working electrode surface. Methods for determination of diclofenac (DCF) using FIA with amperometric detection and simultaneous determination of DCF and codeine (CO) by BIA with amperometric detection have also been developed. The internal standard method was implemented in the flow injection analysis with multiple pulse amperometric detection (FIA-MPA) system by applying a sequence of potential pulses of the working electrode as a function of time. The analyte (+0.80 V/300ms) and internal standard (-0.05 V/400ms) were detected selectively, one at each potential pulse. Significant improvements were obtained in the accuracy of the system when the results before and after normalization (using the internal standard method), were compared. The following errors were calculated, respectively, before and after normalization of the results using the internal standard method. Change in flow rate from 3.0 to 1.0 ml min-1 (-57% e < 1%); volume injection from 300 to 100 μL (-63% and 3%); ionic strength from 0.60 to 0.77 mol L-1 (-44 and 0,2%) and before and after the introduction of air bubbles into the system (-9,6% and 1,7%). A significant improvement was also obtained in the correlation coefficient of the calibration curve in the presence of problems of passivation or contamination of the working electrode. The correlation coefficient was calculated, respectively, as 0,975 and 0,998, before and after the normalization of the results by the IS method. The internal standard method was also applied to correct errors derived from the injection procedure (dispensing rate and injected volume) in batch injection analysis systems (BIA) with amperometric detection when disposable syringes were used. The results obtained before and after normalization of the results by the IS method were the following, respectively: repeatability test (RSD = 6.4 and 1.8%; n = 8), correlation coefficients (R=0.954 and 0.997) and errors obtained in analysis of synthetic samples (E = 9.4 ± 1.5 and 3.5 ± 0.7%; n = 8). The determination of DCF by FIA-MPA was implemented by applying two potential pulses to the BDD electrode using H2SO4 0.1 mol L-1 as supporting electrolyte: (i) + 1.2 V / 50 ms for oxidation and quantification of DCF, and (ii) 0.0 V / 50 ms for constant electrochemical cleaning of the electrode surface. The system showed good stability (RSD = 1.0%, n = 10) and high analytical frequency (135 injections h-1). The method showed a linear response between 5 and 50 μmol L-1 and the detection and quantification limits were as 0.14 and 0.46 mmol L-1, respectively. The proposed method was applied to determine of DCF in pharmaceutical formulations and the obtained results were similar to those obtained by HPLC with a confidence level of 95%. The simultaneous determination of DCF and CO was performed using the following potential pulses: (i) +1.1 V / 50 ms: oxidation and quantification of DCF; (ii) +1.4 V / 50 ms: simultaneous oxidation of DCF and CO, (iii) 0.0 V / 200 ms: for constant electrochemical cleaning of the BDD electrode. The oxidation current from CO was obtained by the difference between currents detected at 1.4 and 1.1 V by using a correction factor. The system showed good stability (RSD = 0.9% and 1.1 for DCF and CO respectively, n = 10) and high analytical frequency (~ 300 injections h-1). The method showed a linear response between 10 and 50 μmol L-1 for DCF and 7.1 and 35.7 μmol L-1 for CO. The LQ and LD were calculated, respectively, at 1.1 and 3.7 μmol L-1, for DCF and 1.0 and 3.3 mol L-1 for CO. The proposed method was applied for simultaneous determination of DCF and CO in pharmaceutical formulations and the obtained results were similar to those obtained by HPLC with a confidence level of 95%. Keywords: Multiple pulse amperometry, FIA, BIA, internal standard, simultaneous analysis, boron doped diamond (BDD), codeine, diclofenac.